Biochemical and structural improvements in ileum and colon with concurrent gut microbiota enhancement through intermittent fasting plasma infusions - Tan, Murat; Ceylani, Taha; Gurbanov, Rafig; Keskin, Seda; Acikgoz, Eda; Sagir, Emrah; Teker, Hikmet Taner (Nature Portfolio, 2025)
This study investigated the impact of intermittent fasting (IF) on older rats by administering plasma from 12-month-old male Sprague Dawley rats subjected to 35 days of IF, with 18-hour fasting intervals followed by 6-hour feeding periods. Over this period, 0.5 ml of plasma was transferred bi-daily to 24-month-old male rats, totaling 15 infusions. Infrared spectroscopy-based qualitative and quantitative analyses revealed significant changes in lipid, protein, and nucleic acid profiles, varying by tissue type and fasting regimen. Histological examination showed structural enhancements in the ileum and colon, along with reduced inflammatory markers TNF-alpha and COX-2, particularly with IF plasma. Additionally, plasma transfer markedly improved gut microbiota composition, increasing alpha diversity and adjusting the Firmicutes to Bacteroidetes ratio. High-Performance Liquid Chromatography results indicated elevated levels of key cecal short-chain fatty acids, suggesting enhanced gut health. These findings highlight the potential of plasma from intermittently fasting rats in modulating biomolecular profiles, intestinal tissue structure, gut microbiota, and SCFA production, offering integrated insights into intestinal health improvements.
Keywords: Intermittent Fasting; Plasma Exchange; Intestinal Tissue; Gut Microbiota; Tnf-Alpha; Cox-2